The Application of Voluntary Information Tools of Environmental Policy in Bulgaria – Possible Solutions for Improvement - Ivanova, Daniela; Haradinova, Anelia (Research Papers, 2019)
In the end of the 20th century a new wave of entirely new instruments of the ecological policy in EU have emerged due to the unveiled shortages in the existent regulative and economic instruments. These voluntary approaches have arisen in response to the need for efficient and flexible instrument for overcoming the limitations and hurdles of the existing policy. They are voluntarily undertaken engagements by the business for improvement of their ecological performance. The conducted research of the voluntary approaches application in Bulgaria has discovered that the companies recognize and implement predominantly the Environment Management System in compliance with the requirements of the international standard ISO 14001. In order to identify potential suggestions for improvement of the voluntary instruments application there have been conducted a qualitative survey – deep interview with a group of stakeholders. The gathered information from the performed 15 interviews has been analysed through the expert evaluation method. Based on that, suggestions to the respective authorities have been developed for encouragement and improvement of the informational instruments application by the companies in the country.
Keywords: Environmental policy; Voluntary informational instruments; Application; Bulgaria